Pengembangan Media P-Camp untuk Menanamkan Kemampuan Pemahaman Konsep Pecahan Campuran Kelas V SDN Gayamsari 02 Semarang - Titik Nurhidayati; Sukamto Sukamto; Husni Wakhyudin (STKIP Andi Matappa Pangkep, 2021)
To stimulate students' enthusiasm for learning and instill students' conceptual understanding of learning materials, interesting and innovative learning media are needed. This study aims to develop P-Camp audiovisual learning media to instill students' conceptual understanding skills in mixed fraction mathematics subjects for class V SDN Gayamsari 02 Semarang. The procedure in this study uses the ADDIE development model from Dick and Carry. The data collected in this study are media expert data and material expert data. The data obtained from the questionnaire were analyzed descriptively. The results of the development of this research in the form of P-Camp audiovisual media. The results of validation by media experts get 84%, validation by material experts get 89%, teacher assessments get 87.50%, and student assessments get 94.69%. This shows that the P-Camp media has been successful in development.